Determinants of saving behaviour among public in Shah Alam / Mohd Kamal Nafiah - Nafiah, Mohd Kamal (Faculty of Business and Management, 2014)
This research aims to study the determinant of saving behaviour among public in Shah Alam. The selected variables will be analyzed to discover the factors that contribute to saving behaviour of public in Shah Alam. This research paper consists of two variables which are independent and dependent variable. Amongst the variables that researcher investigates the variables of parental support, retirement planning, self- control and the factor saving behaviour of people in Shah Alam. The data obtained are be treated as primary data as the researcher use questionnaires to obtain the required information from the respondents. Other than that, some of the related information were obtained from the secondary data such as journals and internet. The variables will be analyzed by using the frequency distribution, descriptive analysis, the reliability analysis and multiple regression analysis. Computer software of Statistical Package for Social Science (SPSS) 2.0 is used in order to analyze the data. The findings indicates that parental support is the most influence variable towards saving behaviour among public in Shah Alam. The research also shows that retirement planning is not significant towards saving behaviour of public in Shah Alam. The researcher also has come out with few recommendations to be taken into consideration. By implementing these recommendations, it will help the public to realize the important to save money and the benefit of it in the future.